Sosialisasi Pengolahan Limbah Roti Menjadi Pakan Ternak Pada UMKM Roti - Syafaatullah, Achmad Qodim; Sariwahyuni; Setyorini, Dwi; Ganing, Melani; Prasetia, Frabowo (TAAWUN, 2023)
The waste generated from the bread-making process has not been utilized optimally. The waste generated from SMEs making bread is only disposed of into the environment. Therefore, to make use of waste to reduce the amount of waste that is disposed of or to provide added value that can be used as a by-product. The method of processing leftover bread from leftover expired bread that is not utilized is fermented into animal feed that can be given to livestock. The target of this dedication is Bread MSME employees in Sumba Opu District, Gowa Regency. There are 3 stages in the implementation of community service operations, namely preparation, implementation, and evaluation. Preparation is carried out by providing raw materials for processing leftover bread left over from soaking bread, mixing with EM4 and granulated sugar, adding bran and meat concentrate, and fermenting. Implementation was carried out by providing opportunities for several participants to ask questions and review the presentations that had been made. The assessment was carried out by filling out a questionnaire given to participants.